Optimization of Remazol Brilliant Blue adsorption process from aqueous solutions using multi-walled carbon nanotube. Issue 28 (14th June 2016) - Arab Markadeh, A.; Rezaee, A.; Rastegar, S.O.; Hossini, H.; Ahmadi, S.; Hoseinzadeh, E.
Abstract: This work aimed to determine the optimum conditions in order to reach the maximum remazol brilliant blue (RBB) removal and maximum adsorption capacity (uptake) in the sorption process from aqueous solution using multi-walled carbon nanotube (MWCNT). Three factors including initial RBB concentration, initial pH, and initial amount of MWCNTs were optimized using response surface methodology at equilibrium time 15 min. Optimized conditions were RBB concentration 8 × 10 −2  mmol/L, initial pH 4.3, and 250-mg MWCNTs. The maximum values for the RBB removal and uptake were 69.06% and 1.1 × 10 −2  mM/g, respectively. Among the three used isotherm models including Langmuir, Freundlich and Temkin, the Langmuir isotherm was best fitted with the experimental data because of its higher coefficient value R 2  = 0.99.